Handbook on Promoting Social Justice in Education 2020
DOI: 10.1007/978-3-030-14625-2_103
|View full text |Cite
|
Sign up to set email alerts
|

Queer Theory/Pedagogy and Social Justice Education

Abstract: Queer theory and pedagogy can inform social justice education in ways that have teachers and researchers question how their teaching practices and philosophies reinforce social norms such as heteronormativity. Queer theory is post-structuralist, and while it is most often used to analyze queer subjects, it can be used to analyze the social and institutional norms in any subject. Queer pedagogy, stemming from queer theory's call to deconstruct heteronormativity and other boundaries, works to expand the way we l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(55 reference statements)
0
4
0
1
Order By: Relevance
“…Queer theory, a term coined by Teresa de Lauretis (1991) , is not so much a theory about queer people, but rather is about queering theory by exposing what is assumed when heterosexuality is viewed as universal ( Bacon, 2006 ; Butler, 2014 ; Halperin, 2003 ; Sedgwick, 2008 ). Queer theorists disrupt binary, heteronormative categories and attempt to explain how oppression is maintained through discourse, silencing, and uses of language that shape how we perform gender and sexual identities ( Pennell, 2020 ). It has been referred to as the theory of anti-normalness ( Halperin, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Queer theory, a term coined by Teresa de Lauretis (1991) , is not so much a theory about queer people, but rather is about queering theory by exposing what is assumed when heterosexuality is viewed as universal ( Bacon, 2006 ; Butler, 2014 ; Halperin, 2003 ; Sedgwick, 2008 ). Queer theorists disrupt binary, heteronormative categories and attempt to explain how oppression is maintained through discourse, silencing, and uses of language that shape how we perform gender and sexual identities ( Pennell, 2020 ). It has been referred to as the theory of anti-normalness ( Halperin, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…La théorie queer, un terme inventé par de Lauretis (1991) , n’est pas tant une théorie sur les personnes queers qu’une perspective théorique queer exposant ce qui est tenu pour acquis lorsque l’hétérosexualité est considérée comme un universel ( Bacon, 2006 ; Butler, 2014 ; Halperin, 2003 ; Sedgwick, 2008 ). Les théoriciens et théoriciennes queers remettent en question les catégories binaires et hétéronormatives et tentent d’expliquer comment l’oppression est préservée par le discours, les voix tues, et les utilisations du langage qui façonnent les manières de performer les identités sexuelles et de genre ( Pennell, 2020 ). Leur théorie a également été décrite comme celle de l’ antinormativité ( Halperin, 2003 ).…”
Section: Méthodologieunclassified
“…Social justice educational leaders must utilize critical consciousness to engage in critical reflection and examine personal biases, privilege, systems of oppression, and discrimination (Lewis & Kern, 2018). Creating safe schools requires disrupting the heteronormative system of schooling (Pennell, 2020), defined by Rubin (in Marchia & Sommer, 2018) as gender and sex being policed through a patriarchal hierarchy of social relations (p. 273).…”
Section: Workplace Climate For Transgender Educatorsmentioning
confidence: 99%
“…Similarly, Theoharis (2007) demonstrated that a key component of social justice educational leadership was increasing “staff capacity by…providing ongoing staff development focused on building equity, developing staff investment in social justice” (p. 235). As Pennell (2020) has asserted, the district and its constituents should examine all aspects of their school district for heteronormativity wherever it exists. Both professional development and policy making are critical methods of support for LGBTQ educators (Wright & Smith, 2015).…”
Section: Significancementioning
confidence: 99%
“…Furthermore, an intersectional approach to education can involve curriculum and pedagogy that reflect the diversity of students' experiences and histories (Goriss-Hunter et al, 2023;Pennell, 2020). For example, incorporating literature written by authors from diverse backgrounds or teaching history that acknowledges the experiences and contributions of marginalized groups.…”
Section: Intersectionality In Educationmentioning
confidence: 99%